My Car is Black, and Yours is White - Galerie Mladych, Brno (Brno : Galerie Mladych, 1994)
Beecroft, Vanessa ; Carocci, Monica ; Friedl, Peter ; Marisaldi, Eva ; Schu, Manfredu ; Strizek, Antonin ; Timoney, Padraig ; Vetrugno, Maurizio ; Weigand, Hans
My Car is Black, and Yours is White, Galerie Mladych, Brno, August-September 1994
boek